A dialogue between an educator and psychologist. Issue 137 (15th April 2013) - Noam, Gil G.; Bernstein‐Yamashiro, Beth
Abstract: This conclusion to the volume presents a dialogue from the perspective of educator and clinician. With examples from professional development and practice, the discussion revolves around teacher training and the role of the administrator in creating a bounded and safe environment in which teachers can develop healthy relationships. It discusses the kind of support teachers need from mental health professionals to grow, reduce the risk of burnout, and obtain help for students when necessary.